2012
DOI: 10.1371/journal.pone.0033054
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cytotoxic, Aggregative Citrobacter freundii

Abstract: Citrobacter freundii is an infrequent but established cause of diarrhea in humans. However, little is known of its genetic diversity and potential for virulence. We analyzed 26 isolates, including 12 from human diarrheal patients, 2 from human fecal samples of unknown diarrheal status, and 12 from animals, insects, and other sources. Pulsed field gel electrophoresis using Xba I allowed us to divide the 26 isolates into 20 pulse types, while multi-locus sequence typing using 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 62 publications
4
80
1
Order By: Relevance
“…C. freundii strain CF74 was isolated from a fecal sample from a goat, as reported previously (26). All strains were grown aerobically at 37°C in Luria-Bertani (LB) medium.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. freundii strain CF74 was isolated from a fecal sample from a goat, as reported previously (26). All strains were grown aerobically at 37°C in Luria-Bertani (LB) medium.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of in vitro adhesion to host cells was performed using the human epidermoid carcinoma cell line HEp-2 (CCC0068; Beijing Union Medical College cell resource center), as previously described (26). Infections were performed at a multiplicity of infection (MOI) of 100:1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study which pertained to the virulence markers in Citrobacter freundii was conducted by Li Bai et al, [8] in 2012, who found that the aggregative adherence and cytotoxicity played an important role in diarrhoea which was caused by the same organism. Taylor [9] reviewed that the bacteria are killed by normal human serum through the lytic activity of the alternate complement system.…”
Section: Discussionmentioning
confidence: 99%